The Role of Integrated Assessment Teams in Narcotic Abuse Rehabilitation - Chandra, Tofik (LifeSciFi, 2021)
Legal issues in terms of the development of criminal law on the role of assessment by the National Narcotics Agency in settling cases. The assessment process occupies an important position to determine whether narcotics abusers can carry out medical and social rehabilitation. This research delves into the pivotal role played by integrated assessment teams in determining the rehabilitation process for individuals struggling with narcotics abuse. Through the lens of normative legal research and qualitative analysis, this study underscores the equitable treatment that integrated assessments afford to suspected narcotics abusers, ultimately facilitating early rehabilitation placements. The research findings serve as a compass for law enforcement agencies in making informed decisions regarding whether an individual should undergo rehabilitation or be placed in detention, contingent upon their involvement in narcotics-related activities. To bolster this process, the study recommends the implementation of more stringent regulations, making it mandatory for all law enforcement officers to adhere to the integrated assessment procedure. This emphasis on procedural consistency aims to prioritize justice and legal equity for individuals impacted by narcotics abuse within the legal framework